Structural Damage Identification Using a Multi-stage Gravitational Search Algorithm (Journal of Civil Engineering Researchers, 2024)
A multi-stage gravitational search algorithm (MSGSA) is proposed here to solve the optimization-based damage detection of structural systems. Natural frequency changes of a structure are considered as a criterion for damage occurrence. Finite element method and structural dynamic principles are also employed to evaluate the required natural frequencies. The structural damage detection problem is first transformed into a standard optimization problem dealing with continuous variables, and then the MSGSA is utilized to solve the optimization problem for finding the site and severity of damage. In order to assess the performance of the proposed method for damage identification, an example with experimental data and two numerical examples with considering measurement noise are considered. All the results demonstrate the effectiveness of the proposed method for accurately determining the site and extent of multiple structural damage. Also, the performance of the MSGSA for damage detection compared to the standard gravitational search algorithm (GSA) is confirmed by examples.
Keywords: Damage detection; Natural frequencies; Finite element analysis; Optimization method; Multi-stage gravitational search algorithm